Konstruk Loyalitas Konsumen Mobil Merek Hyundai Ditinjau Dari Aspek-Aspek Yang Menyertainya - Abdullah, Muhammad (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2024)
The Hyundai car brand has the most enormous average sales growth from 2019-2022 compared to all car brands in Indonesia, even though the car brand is not from Japan. Based on these exciting facts, this study aims to understand, know more deeply, and analyze the effect of product quality and service quality on customer satisfaction and their impact on the consumer loyalty of the owner of the Hyundai car brand. The sample in this study was determined as many as 95 respondents using the purposive sampling method with the criteria of being an owner of a Hyundai brand car located in Jakarta, the data obtained from the respondents was collected using a questionnaire distributed via a google form. The analysis technique used in this study is descriptive analysis technique and inferential analysis using SmartPLS 4. The results of hypothesis testing are as follows: (1) product quality has a positive and significant effect on customer satisfaction, (2) service quality has a positive and significant effect on customer satisfaction, (3) product quality has a positive and significant effect on customer loyalty, (4) service quality has a positive and significant effect on customer loyalty, (5) customer satisfaction has a positive and significant effect on customer loyalty, (6) product quality through satisfaction mediation customers have a positive and significant effect on customer loyalty, (7) service quality through the mediation of customer satisfaction has a positive and significant effect on customer loyalty.